Gaze Cuing Effects in Peripheral Vision - Yokoyama, Takemasa; Takeda, Yuji (Frontiers in Psychology, 2019)
When we see another person’s gaze, spatial attention shifts toward the gaze direction. Thus, a gaze perceiver can more quickly respond to a forthcoming target when it appears in a direction of a gaze giver than when it does not. This phenomenon is termed the gaze cuing effect. Previous studies have investigated the gaze cuing effect only in foveal vision; hence, it remains unclear whether the gaze cuing effect is induced when a face is presented in peripheral vision. This is an important issue because in our daily lives we communicate not only with people in front of us but also with those in our periphery. To tackle this question, we manipulated vertically aligned locations of a facial stimulus (i.e., a face stimulus appeared above or below the center fixation), and tested the extent to which a gaze cuing effect, conveyed by gaze shifts of another, would is observed in the periphery. The facial stimulus was located 0°, ±2.5°, ±5.0°, ±7.5° of the visual angle from the center of the display, and a target was presented 5.6° to the left or right of the center of the display. In Experiment 1, when participants responded to the location of an abrupt onset of a target (i.e., localization task), we observed significant gaze cuing effects when a facial stimulus was located 0°, ±2.5°, and ±5.0°, but not ±7.5°. In Experiment 2, we replicated the findings in Experiment 1 if participants pressed a key only when a target appeared (i.e., detection task). In Experiment 3, we used adjusted sizes of facial images based on the cortical representations and manipulated eye directions of the facial images oriented toward the possible target locations; it resulted in enlarged effective field of view for gaze cuing effects. The study reveals that gaze cuing effects can appear even in peripheral vision and within a vertical distance of 5.0° of the visual angles, but the effective field of view is expanded when the facial image is adjusted based on the cortical representations, and eye gaze directly looks at the possible target locations.